Analisis Kebutuhan Robot Rehabilitasi Pasien Pasca Stroke dengan Menggunakan Metode Kano - Hasan Mastrisiswadi; Herianto Herianto (Jurnal Ilmiah Teknik Industri, 2016)
Product developments of post stroke rehabilitation robot have being done either by local universities or by foreign ones. In this development processes, customer needs were identified prior to the use of QFD method, assuming that improved performance of customer needs linearly affects satisfaction level. This assumption frequently does not fit real condition in the market, wherein customer satisfaction on certain needs dramatically increases by an improvement on their performance and, on the other hand, improved performance on other needs does not affect customer satisfaction at all. In this research, we conclude that almost all of attributes under study belong to one-dimentional categories. Exceptions are associated with portable attribute that belong to must-be categoris and moveable attribute that belong to attractive categories. Moreover, price attribute will affect consumer satisfaction the most given it is fullfilled and control attribute will influence customer dissatisfaction the most if it is not fullfilled.